Improvement of capacity in bending by the use of FRP layers on RC beams - Bulavs, Felikss; Radinsh, Ivars; Tirans, Normunds (Journal of Civil Engineering and Management, 2005)
Carbon‐filled plastic bands are more extensively used for strengthening the permanently exploited curved elements. As a result, the bending rigidity of the element is increased and the crack formation process is changed. Investigation of these problems is carried out basing on the model of laminated material, in which the mechanical properties of separate layers may have discreete different values depending on the external load volume. Practical calculations are made by numerical methods which make it possible to follow up the origin of the crack formation in the concrete, by taking into account its non‐linear deformation character. The work deals with the analysis of the beam strengthening specific character under unloaded and loaded conditions. Testing of the results is performed by using 2 m long reinforced concrete beams strengthened with carbon‐filled plastic bands. Gelžbetoninių sijų laikomosios galios padidinimas taikant dispersiškai armuotus plastiko lakštus Santrauka. Anglies pluoštu armuoti plastiko lakštai yra dažniausiai naudojama medžiaga ilga laika eksploatuojamiems kreivos formos elementams. Ši medžiaga padidina elemento standuma, keičiasi plyšiu vystymosi procesas. Sprendžiant šia problema taikytas sluoksniuotuju medžiagu modelis, kuriame kai kurie sluoksniai (tai priklauso nuo apkrovimo lygio) gali pasižymeti skirtingomis mechaninemis savybemis. Praktiniai skaičiavimai atlikti taikant skaitinius metodus, kurie leidžia ivertinti betono pleišejima bei netiesines deformacijas. Pateikta sustiprintosios sijos analize nukrovimo ir apkrovimo salygomis. Atlikta 2 m ilgio gelžbetonines sijos, sustiprintos anglies pluoštu armuoto plastiko lakštais, analize. Raktiniai žodžiai: sija, ilinkis, gelžbetonis, skaičiavimo metodai, anglies lakštai, plyšiu vystymasis, tiltas. First Published Online: 14 Oct 2010